Reliability and validity of the Chinese version of the Gatos Clinical Test questionnaire in patients with severe dementia - Zhao, Yan; Shen, Xuhui; Mao, Dandan; Xu, Meiying; Li, Shasha; Wang, Lin; Zhao, Xueyang (Frontiers in Psychology, 2025)
BackgroundThe Gatos Clinical Test (GCT) Questionnaire is an effective tool to evaluate the vitality, survival, and maintenance of basic skills potential in patients with severe dementia. However, it has not yet been verified for use in China.ObjectivesThis study aims to adapt the GCT questionnaire across cultures and utilize a cross-sectional design to verify its reliability and validity in people with severe dementia in China.MethodsThe original questionnaire was translated into Chinese according to the Brislin two-person translation-return translation method. This study conducted a questionnaire survey on 276 severe dementia patients in China. The patients were 52 to 88 years old, with an average age (78.34 ± 6.42) years old, with 45.3% of men (n = 125) and 54.7% of women (n = 151). The patients completed the Chinese version of GCT questionnaire and Mini-Mental State Examination and used the item distribution, critical ratio, and correlation coefficient to screen the items. The content validity index was used to evaluate the content validity of the questionnaire. Exploratory factor analysis and confirmatory factor analysis were used to test the construct validity of the questionnaire. The reliability of the questionnaire was evaluated by Cronbach’s alpha coefficient, test–retest reliability and inter-rater reliability evaluation.ResultsThe Chinese version of the GCT questionnaire consisted of 14 items. Factor analysis extracted three common factors with a cumulative variance contribution rate of 65.513%. Confirmatory factor analysis demonstrated satisfactory construct validity for the questionnaire. The questionnaire’s content validity index was 0.91. Cronbach’s alpha coefficient was 0.898, test–retest reliability was 0.959, and inter-rater reliability was 0.986.ConclusionThe Chinese version of the GCT questionnaire has good reliability and validity and can be an effective tool for clinical and community healthcare professionals to assess patients with severe dementia.